WAYS TO IMPROVE THE REGIONAL POLICY OF UZBEKISTAN’S INDUSTRY - Maftuna Norpulatovna Farmonova (Web of Journals Publishing, 2025)
This article presents an in-depth analysis of the regional development of the industrial sector in the Republic of Uzbekistan, highlighting disparities among regions based on statistical data. Practical proposals are developed to balance industrial policy at the regional level, establish competitive industrial clusters, and increase investment activity. Keywords: industrial policy, regional development, economic balance, industrialization, clustering, state programs.